Kinetically Stabilized Hafnia Ferroelectric of Al-Doped HfO2 Film by Fast Ramping and Fast Cooling Process - Zhang, Lingwei; Kim, Giuk; Lee, Sangho; Shin, Hunbeom; Lim, Youngjin; Kim, Kang; Oh, Il Kwon; Ko Park, Sang Hee; Ahn, Jinho; Jeon, Sanghun (IEEE Transactions on Electron Devices, 2024)
Hafnia-based ferroelectrics (FEs) can be stabilized via careful engineering, both kinetically and thermodynamically. Especially, the fast cooling process has been regarded as an efficient approach for kinetically maximizing the phase transition to the orthorhombic (o-) phase from the tetragonal (t-) phase, which stabilizes thermodynamically during crystallization annealing. However, accurately controlling the cooling period for fast cooling procedures is challenging, resulting in unreliable and nonreproducible outcomes and interpretation. Thus, until now, comprehending its effects has mainly relied on modeling efforts in the field of material science. Here, for the first time, we experimentally validate the fast-cooling effect with Al:HfO2 FEs, based on the novel equipment ensuring both reliability and reproducibility. In addition, it enabled us to investigate the impact of the fast cooling process on the phase, domain size, and interface quality of FEs through various electrical analyses. The fast cooling technique facilitates the transition from the t-phase to the desired o-phase, inducing significantly higher remanent polarization values of 2Pr (35.31 µC/cm2) and improved subloop characteristics. In contrast, slow cooling (2Pr of 9.50 µC/cm2) leads to poor subloop properties. Given that a fast cooling procedure is useful for stabilizing the FE o-phase in thin films, we believe that our reliable annealing procedure and significant experimental findings can provide a foundation for future studies in hafnia FE material and memory devices.
Keywords: Al-doped; Al-doped HfO2; Cooling process; Fast ramping fast cooling; Fast-ramping; Ferroelectric; HfO 2; Metal capacitors; Metal-ferroelectric-metal capacitor; Metal-ferroelectric-metals; Al-doped HfO2; annealing; fast ramping fast cooling (FRFC); ferroelectric (FE); metal–FE–metal (MFM) capacitors